2013
DOI: 10.1017/jan.2013.5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of two lucerne-based forage feeds, FiberProtect® and FiberEdge® on Equine Gastric Ulcer Syndrome in horses

Abstract: Equine Gastric Ulcer Syndrome (EGUS) is extremely prevalent in both racing and non-racing horse populations. The exact aetiology of EGUS is unclear but many stress related risk factors have been implicated including the feeding of grain-based diets. Current treatment techniques often necessitate drug therapy which, when added to feed costs, can be expensive and may have a detrimental effect on digestion due to the mode of action of these therapies. The following experiment set out to investigate if feeding fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Multiple feed supplements are currently available to horse owners; however, few have been scientifically evaluated (Cargile and others 2004, Frank and others 2005, Huff and others 2012, Stowers and others 2013). A commercial product containing a pectin-lecithin complex (Pronutrin, Boehringer Ingelheim, Ingelheim, Germany) is available in South Africa and is widely used for treatment of gastric ulcers in horses.…”
mentioning
confidence: 99%
“…Multiple feed supplements are currently available to horse owners; however, few have been scientifically evaluated (Cargile and others 2004, Frank and others 2005, Huff and others 2012, Stowers and others 2013). A commercial product containing a pectin-lecithin complex (Pronutrin, Boehringer Ingelheim, Ingelheim, Germany) is available in South Africa and is widely used for treatment of gastric ulcers in horses.…”
mentioning
confidence: 99%
“…The buffering ability of alfalfa hayegrain diet results from its high crude protein content [47]. The mechanism of action for gastric acid inhibition is that when alfalfa is consumed, there is increasing calcium absorption, which results in higher level of extracellular calcium, which influences the calcium concentration in gastric acideproducing cells [48].…”
Section: Alfalfa Haymentioning
confidence: 99%
“…Alfalfa hay could also be used to prevent and heal gut lesions. Stowers et al [48] reported that fermented alfalfa prevented and healed gastric ulcers at 40%e60% and 70%e100% dry matter intake, respectively. This is because alfalfa hay has a prolonged effect on pH reduction.…”
Section: Alfalfa Haymentioning
confidence: 99%
“…Feeding alfalfa hay to yearlings for 28 days is associated with a lower ulcer severity score than feeding costal Bermudagrass hay 14 . Feeding alfalfa forage‐based feeds for 42 days reduces ulcer severity scores in both the glandular and nonglandular areas in horses not at work 15 . However, these findings remain controversial as more severe mucosal lesions at the pylorus are found in weanling horses fed alfalfa chaff for 16 days after weaning 16 .…”
Section: Introductionmentioning
confidence: 99%